Strategi Guru PPKn Dalam Meningkatkan Kedisiplinan Siswa di SMP Muhammadiyah 2 Manado - Sallao’, Edna La’bi’; Lonto, Apeles Lexi; Biringan, Julien (CV. Kurnia Grup, 2025)
Discipline is one of the important aspects in realizing an orderly, safe, and comfortable school environment for all school residents. However, the reality in the field shows that there are still students who have not fully displayed a disciplined attitude. This condition requires a special strategy from educators, especially PPKn teachers who have a great responsibility in shaping student character, including discipline attitudes. This study aims to analyze the strategies used by PPKn teachers in instilling discipline in Muhammadiyah 2 Manado Junior High School and to reveal the factors behind students' indisciplined behavior. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. The results of the study showed that teachers implemented several strategies, including good classroom management, habituation of discipline, strict attitude in giving rules, and the application of educational sanctions. The dominant factors that affect the lack of discipline of students come from disharmony in the family and the bad influence of peer association. Based on these findings, it can be concluded that improving student discipline requires synergy from various related parties.